The Eyewitness visual dictionary of flight. (New York : Dorling Kindersley, 1992)
Text and labeled illustrations depict a variety of historic and modern aircraft and their components, as well as aviation-related equipment.
Includes index.
Keywords: Aeronautics -- Terminology; Aeronautics -- Dictionaries; Flight; Picture dictionaries, English